Memahami Pengawasan dan Evaluasi dalam Administrasi Pendidikan - Fadillah Annisak; Fenika Ardiyani; Irlyanova Sabina (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
Supervision is the overall activity of supervising, checking, coordinating and controlling all activities so that they take place in accordance with established plans and desired results. Evaluation is a form of planned process of determining the condition of an object using instruments while the results are used as a benchmark for comparison with what was planned to obtain conclusions. The research method used in this article is library research, which is a way to collect data by understanding and studying theories from various literature related to the research topic. The results of the analysis show the meaning of educational supervision, the purpose of educational supervision, the function of educational supervision, the meaning of evaluation, the purpose of evaluation in education and the function of evaluation in education in order to achieve a clear direction in understanding supervision and evaluation in educational administration.